The Utility and Development of the Competencies of Professional Psychology Rating Scales (COPPR) - Rice, Kylie; Schutte, Nicola S.; Cosh, Suzanne M.; Rock, Adam J.; Banner, Stephanie E.; Sheen, Jade (Frontiers in Education, 2022)
Competency-based professional psychology training is now common practice in many countries. An implication of competency-based training is the need to assess practitioner competence across multiple domains of practice; however, standardised measures of competence are limited. In Australia, currently there is no standardised, quantitative measure of professional competencies at registered psychologist level. The absence of a measure has implications for education, training, practice, and research in professional psychology. To address this gap, this article provides a conceptual overview of the utility and development of the Competencies of Professional Psychology Rating scales (COPPR), including the process of initial pre-test, pilot, and review. This developmental process resulted in the thematic identification of competencies within 11 domains of practice, and the creation of both COPPR-Self report and COPPR-Observer report versions. The pre-test provided content validity for the COPPR, and the initial results of the pilot test suggest strong convergent and divergent validity. The measure differentiated between novice and experienced practitioners, suggesting the scale is appropriate for use across career stages. The COPPR scales address the need for a standardised and quantitative measure across multiple domains of practice at registered psychologist level in Australia. The COPPR scales are intended to have utility across professional psychology student and supervisee performance evaluation, self-reflection for psychologists in practice, educational evaluation at professional psychology level, and various research contexts.